Book Review, Man in the Mangroves: The Socio Economic Situation of Human Settlements in Mangrove Forest - Aprilani Soegiarto (Universitas Gadjah Mada, 1988)
Book Review, Man in the Mangroves: The Socio Economic Situation of Human Settlements in Mangrove Forest